The top of the Olduvai Subchron in a high-resolution magnetostratigraphy from the West Turkana core WTK13, hominin sites and Paleolakes Drilling Project (HSPDP) - Sier, M; Langereis, C; Dupont-Nivet, G; Feibel, C; Joordens, J; van der Lubbe, J; Beck, C; Olago, D; Cohen, A (Elsevier, 2017)
One of the major challenges in understanding the evolution of our own species is identifying the role climate change has played in the evolution of hominin species. To clarify the influence of climate, we need long and continuous high-resolution paleoclimate records, preferably obtained from hominin-bearing sediments, that are well-dated by tephro- and magnetostratigraphy and other methods. This is hindered, however, by the fact that fossil-bearing outcrop sediments are often discontinuous, and subject to weathering, which may lead to oxidation and remagnetization. To obtain fresh, unweathered sediments, the Hominin Sites and Paleolakes Drilling Project (HSPDP) collected a ~216-meter core (WTK13) in 2013 from Early Pleistocene Paleolake Lorenyang deposits in the western Turkana Basin (Kenya). Here, we present the magnetostratigraphy of the WTK13 core, providing a first age model for upcoming HSPDP paleoclimate and paleoenvrionmental studies on the core sediments. Rock magnetic analyses reveal the presence of iron sulfides carrying the remanent magnetizations. To recover polarity orientation from the near-equatorial WTK13 core drilled at 5°N, we developed and successfully applied two independent drill-core reorientation methods taking advantage of (1) the sedimentary fabric as expressed in the Anisotropy of Magnetic Susceptibility (AMS) and (2) the occurrence of a viscous component oriented in the present day field. The reoriented directions reveal a normal to reversed polarity reversal identified as the top of the Olduvai Subchron. From this excellent record, we find no evidence for the ‘Vrica Subchron’ previously reported in the area. We suggest that outcrop-based interpretations supporting the presence of the Vrica Subchron have been affected by the oxidation of iron sulfides initially present in the sediments -as evident in the core record- and by subsequent remagnetization. We discuss the implications of the observed geomagnetic record for human evolution studies.